The Prevalence of Demodex folliculorum and Demodex brevis in Cylindrical Dandruff Patients - Yuan, Jin; Wang, Bowen; Peng, Lulu; Li, Saiqun; Tan, Yiwei; Zhong, Jing; Deng, Yuqing (Journal of ophthalmology, 2019)
Purpose. To compare the prevalence of and factors associated with Demodex brevis and Demodex folliculorum in patients with cylindrical dandruff (CD group) and healthy controls. Methods. Eyelashes were taken from 1680 patients with CD and 1700 healthy controls in China from March 2015 to May 2017. All patients underwent a complete eye examination, and Demodex spp. were counted. The prevalence was analyzed according to age, gender, and clinical features. Results. Mean patient age was 42.93 ± 16.52 (3–88) and 39.4 ± 13.6 (7–81) years old in the CD and healthy control groups, respectively. In the CD and healthy groups, the positive rate for Demodex folliculorum was 27.92% and 8.47%, respectively, while that for Demodex brevis was 31.67% and 6.65%, respectively. In the CD group, the prevalence of Demodex brevis was higher than that of Demodex folliculorum, no matter in the females (33.65% versus 29.01%) or the males (28.54% versus 23.88%) in the CD group. Moreover, the numbers of Demodex folliculorum and Demodex brevis were significantly and positively correlated with age, in both children and old patients (both P<0.001), as well as with the severity of eyelid congestion (all P<0.05). Conclusions. In a large sample population, the prevalence of Demodex brevis and Demodex folliculorum was higher in the CD group than in healthy volunteers. In addition, the severity of eyelid congestion might be exacerbated by the number of Demodex spp., which may therefore provide a good clinical reference and objective guide.